Importance of examining particle movements in modelling ballast bed via discrete element method. Issue 5 (3rd September 2022) - Fu, Longlong; Zheng, Yuexiao; Tian, Zhekan; Huang, Shihao; Zhou, Shunhua
ABSTRACT: The discrete element method is widely adopted to investigate the micro-mechanism of degradation and reinforcement of ballast tracks. Generally, numerical parameters of ballast particles are examined by macro characteristics obtained in field or indoor tests, while particle-scale responses are rarely examined due to the difficulties in practical measurement. In this study, we demonstrate the importance of examining particle movements in modelling ballast bed via discrete element method. A previous laboratory model test is repeated via Particle Flow Code, where 25 sets of damping coefficients are assigned. The results show that the variation of damping coefficients has more significant influence on particle movements than the macroscopic behaviours of ballast and ballast beds. According to the three-dimensional motion characteristics of ballast particles obtained using a SmartRock sensor, the appropriate local damping constant and critical contact damping ratio are suggested for typical loading frequencies.